Peran Pancasila Dalam Membentuk Identitas Nasional Indonesia: Perspektif Historis dan Sosial - Abdusshomad, Alwazir (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Indonesia, with its diversity of ethnicities, cultures, and religions, faces the challenge of forming a solid national identity. Pancasila, as the state ideology, serves as an essential foundation for integration. The purpose of this research is to investigate the role of Pancasila in shaping Indonesia's national identity, particularly in historical and social contexts. The focus is on analyzing how Pancasila responds to the need for an inclusive ideological framework, and how its principles provide a social foundation for harmonious living. This research aims to provide a deep understanding of the importance of Pancasila in building a strong and inclusive national identity in Indonesia. The method used is library research. The results show that Pancasila plays a central role in shaping Indonesia's national identity, serving as a philosophical cornerstone that fosters nationalism and provides a framework for understanding and embracing differences. As a response to the need for an inclusive ideological framework, Pancasila, introduced by the Founding Fathers such as Soekarno and Mohammad Hatta, becomes the foundation of a national identity that reflects the spirit of unity. Its social principles, such as mutual cooperation and consensus-building, also play a crucial role in addressing the challenges of diversity, guiding Indonesian society towards harmonious living.